Policy extrusion kazakhs from the inside of the boundary line of Orenburg region of the XIX n the second quarter of the XIX century - Kabuldinov Z. Е. (Journal of Oriental Studies, 2016)
This article describes the imperial policy of expulsion of Kazakhs of the Orenburg edge of the inner part of the boundary line in the second quarter of the XIX century. In particular, the research shows the system functioning ticketing system introduced in 1817 to dramatically ogranichneniya access to the inner side of the Kazakhs. The process of host cities in the impoverished Kazakh Orenburg province. Paper is based on new archival materials and is addressed to specialists in the new period of national history.